Strategic translanguaging patterns in asynchronous vocational ELT discussions: A qualitative case study - Mutiaraningrum, Ira; Salam, Urai; Mahendra, Made Wahyu; Nugroho, Arif; Lestari, Sri; Sulaiman, Sulaiman (Journal of English Language Teaching Innovations and Materials (Jeltim), 2026)
This study aims to explore how technology-mediated pedagogical translanguaging practices serve as a space for meaning-making in online discussion forums through Google Classroom. It focuses on how vocational students construct meaning during online discussions by strategically mobilizing multilingual resources to negotiate ideas with peers. Employing a qualitative case study approach, this study focused on how Indonesian vocational college students constructed meaning. This study involves a thread of 114 comments discussed by 24 7th-semester students from the Fisheries and Maritime Agribusiness Study Program at a vocational college. The data collected were excerpts from the online discussion forum. They were analyzed using thematic analysis through a translanguaging lens. This study reveals that translanguaging functions as a pedagogical rationality, as it occurs functionally to explain concepts, negotiate ideas, and express stance during discussions. Students generally use English to express formal feelings, self-assess, discuss abstract concepts, and use general terms. Bahasa Indonesia explains processes and difficulties, concretize English concepts, and construct sentences that show cause-and-effect relationships. Meanwhile, Malay is used to express personal feelings and to affirm student identity. It also serves as a language of persuasion and a marker of everyday fluency. Translanguaging as a pedagogical resource in a vocational ELT context serves distinct communicative and cognitive roles in a technology-mediated environment. This study contributes to translanguaging research by demonstrating how multilingual resources function strategically in vocational ELT within asynchronous digital environments.